Acute mediastinal bleeding during vacuum‐assisted closure - Vos, Roemer J (Int Wound J, 2012)
Vacuum‐assisted closure is commonly used to treat post‐sternotomy mediastinitis. Several studies show improved outcome using vacuum‐assisted therapy; however, risks using negative pressure should not be underestimated. We describe two cases of acute mediastinal bleeding during vacuum treatment for post‐sternotomy mediastinitis and discuss preventative measurements.